NOD2/CARD15 gene influences disease behaviour but not IBD susceptibility in a Moroccan population - Serbati, Nadia; Badre, Wafaa; Diakite, Brehima; Nadifi, Sellama (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: IBD (Crohn’s disease and Ulcerative Colitis) is chronic and multifactorial disease of the gastrointestinal tract. Till now, his pathogenesis remains unclear. It involves innate immunity, environmental component and genetic predisposition. Polymorphisms in NOD2/CARD15 have been implicated in Crohn’s disease in several ethnic groups. The purpose of our study was to assess the frequency of the three major variants of this gene (Leu1007fsinsC, R702W, and G908R) in Moroccan IBD patients and to determine a possible effect of these variants on Disease’s phenotype and clinical course. Materials and Methods: A total of 96 Moroccan unrelated IBD patients and 114 healthy controls were genotyped (PCR-RFLP method) for the three main polymorphisms. Results: In this study, no correlation was found between NOD2/CARD15 polymorphisms and ulcerative colitis or Crohn’s disease in our population. Nevertheless, 3020insC (Leu1007fsinsC) variant was associated to a structuring behaviour on CD patients. Conclusion: These findings suggest that NOD2/CARD15 influences disease behaviour but not susceptibility to crohn’s disease in Moroccan IBD patients.